Microprudential Indicators of Financial System Stability: An AHP Approach - Rani, Lina Nugraha; Rusydiana, Aam Slamet; Hasib, Fatin Fadhilah (SMART Insight, 2023)
In general there are two indicators of financial system stability, namely microprudential and macroprudential. Among macroprudential indicators are economic growth, balance of payments, inflation rate, interest and exchange rates, crisis contagion effect, and many others. Different from the previous researches concerning financial system stability measurement, this research will use the financial and banking practitioners' perspective regarding the leading indicator in measuring financial system stability so that we can presumably determine the real leading financial stability indicator for the current situation using Analytic Hierarchy Process (AHP) method. This study will look at the indicator of financial system stability from a microprudential perspective in Indonesia. The results show that based on the results of interviews with experts/banking practitioners, the 3 (three) most important aspects are Capital & Asset (0.187), Profitability (0.186) and Asset Quality (0.177). Important indicators of financial system stability from the next microprudential aspect are Liquidity (0.176), Market-based Indicators (0.139) and finally Risk Sensitivity (0.136). The Macroprudential Policy and microprudentials issued by Bank Indonesia as the central bank that has full authority, play an important role in maintaining Financial System Stability (SSK) in Indonesia.